2021
DOI: 10.3390/jcm10163709
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype Rearrangement in Response to Tumor Excision May Be Related to the Risk of Biochemical Recurrence in Prostate Cancer Patients

Abstract: Background: Prostate cancer (PCa) is known to exhibit a wide spectrum of aggressiveness and relatively high immunogenicity. The aim of this study was to examine the effect of tumor excision on immunophenotype rearrangements in peripheral blood and to elucidate if it is associated with biochemical recurrence (BCR) in high risk (HR) and low risk (LR) patients. Methods: Radical prostatectomy (RP) was performed on 108 PCa stage pT2–pT3 patients. Preoperative vs. postoperative (one and three months) immunophenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
5
0
3
Order By: Relevance
“…Apenas 3 artigos realizaram análises de sobrevida e/ou estudos de correlação entre as células NK e a recorrência bioquímica. [8][9][10] Três artigos também descreveram valores de PSA, mas em apenas um deles houve análise pormenorizada, estabelecendo correlação entre a população das células NK e/ou sua atividade e fatores prognósticos já utilizados na prática clínica como escore de Gleason e estadio TNM.9…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Apenas 3 artigos realizaram análises de sobrevida e/ou estudos de correlação entre as células NK e a recorrência bioquímica. [8][9][10] Três artigos também descreveram valores de PSA, mas em apenas um deles houve análise pormenorizada, estabelecendo correlação entre a população das células NK e/ou sua atividade e fatores prognósticos já utilizados na prática clínica como escore de Gleason e estadio TNM.9…”
Section: Resultsunclassified
“…de sua atividade como fator prognóstico. [8][9][10][11][12] Com exceção do trabalho de Bosas e colaboradores, foi demonstrado aumento da população das células NK ou de sua atividade após PTR e uma correlação positiva entre aumento da população de células NK pós-operatória ou da sua expressão e aumento da sobrevida livre de doença/recidiva bioquímica.…”
Section: Figura 1 Fluxograma Dos Artigos Revisadosunclassified
“…Their functions include the inhibition of CLTs through various mechanisms (e.g., producing reactive oxygen species (ROS) or interactions with the T cell receptor [TCR]), suppressing natural killer (NK) cells, and Tregs induction [ 56 , 57 , 58 , 59 , 60 ]. The level of MDSCs correlates with the stage of PC and applied treatment, as well as with the serum levels of crucial inflammatory mediators—IL-6 and IL-8 [ 61 , 62 , 63 ].…”
Section: Immunological Background Of Prostate Cancermentioning
confidence: 99%
“…CRS has itself been proposed to be a form of immunotherapy [ 208 ]. Subsequent studies have confirmed that tumor resection can re-activate the native immune system to an anti-tumor phenotype [ 209 , 210 , 211 ]. In fact, catumaxomab, a trifunctional antibody, was approved in Europe for intraperitoneal use to treat malignant ascites, has demonstrated promise to directly treat GI-derived PC, and is undergoing additional evaluation of efficacy for curative intent (NCT04222114, NCT01815528, and NCT01246440) [ 212 , 213 , 214 , 215 , 216 ].…”
Section: Landmark Efficacy Studiesmentioning
confidence: 99%